Wolf’s isotopic response of eczema after herpes zoster infection: case report and literature review - Zhao, Yirui; Zhang, Min; Chen, Xuanlin; Guo, Shuping; Liu, Hongye (Frontiers in Medicine, 2026)
Wolf’s post-herpetic isotopic response (PHIR) refers to the development of new cutaneous conditions, such as tumors, infections, or immune-mediated diseases, at the site of a previously healed herpetic eruption. The exact pathogenesis of Wolf’s PHIR remains incompletely understood. Four hypotheses have been proposed regarding the mechanism of postherpetic inflammatory isomorphic reactions: viral, immunological, vascular, and neurological. In this case, we show that a patient with eczema developed it at the original site following the resolution of the herpes zoster infection. After 2 weeks of systemic oral glucocorticoid treatment, the skin lesions improved significantly, and there was no recurrence during the 3-month follow-up.